2011
DOI: 10.24839/1089-4136.jn16.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Personal Prejudice: Examining Relations Among Trait Characteristics, Parental Experiences, and Implicit Bias

Abstract: Psi chi central office P.o. box 709 chattanooga, tn 37401-0709 (423) 756-2044 www.psichi.org ABoUT PSI CHI Psi Chi is the International Honor So ci ety in Psychology, found ed in 1929 for the pur pos es of encouraging, stim u lat ing, and maintaining ex cel lence in schol ar ship, and advancing the sci ence of psy chol ogy. Mem ber ship is open to gradu ate and under gradu ate men and women who are mak ing the study of psy chol ogy one of their major interests and who meet the min i mum qual i fi ca tions. Psi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Deme triou (2013) found that, in Cyprus, xenophobia, or an intense and irrational dislike of people from other countries and groups correlated with greater perceived parental rejection. On the other hand, paternal warmth has been linked to less positive attitudes toward Muslims, an outgroup (Brayko, 2011). Demetriou (2013), Brayko (2011), and the current research suggested a link, still unclear, between ethnic attitudes and parental acceptance rejection, warranting further research.…”
Section: Parental Acceptance-rejection and Ethnic Attitudesmentioning
confidence: 61%
See 1 more Smart Citation
“…Deme triou (2013) found that, in Cyprus, xenophobia, or an intense and irrational dislike of people from other countries and groups correlated with greater perceived parental rejection. On the other hand, paternal warmth has been linked to less positive attitudes toward Muslims, an outgroup (Brayko, 2011). Demetriou (2013), Brayko (2011), and the current research suggested a link, still unclear, between ethnic attitudes and parental acceptance rejection, warranting further research.…”
Section: Parental Acceptance-rejection and Ethnic Attitudesmentioning
confidence: 61%
“…Although many theories exist to explain in and outgroup attitudes, the research linking in and outgroup attitudes with parenting, specifically parental acceptance and rejection, is sparse. Specifically, research has linked strong identification with parents to similar racial and prejudicial attitudes (Sinclair et al, 2005), as well as paternal warmth with negative outgroup attitudes (Brayko et al, 2011). Further research has also found that individuals being raised by rejecting, neglectful, or abusive parents are more likely to have prejudiced attitudes (Duckitt, 2001) and that xenophobia is correlated with greater perceived parental rejection (Demetrio, 2013).…”
Section: Ethnicity and Attitudes Toward In-and Out-groupsmentioning
confidence: 99%